The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2004
DOI: 10.1063/1.1689151
|View full text |Cite
|
Sign up to set email alerts
|

Angular dependence of switching properties in single Fe nanopillars

Abstract: The continued increase in areal densities in magnetic recording makes it crucial to understand magnetization reversal in nanoparticles. We present finite-temperature micromagnetic simulations of hysteresis in Fe nanopillars with the long axis tilted at angles from 0 degrees to 90 degrees to the applied sinusoidal field. The field period is 15 ns, and the particle size is 9 × 9 × 150 nm. The system is discretized into a rectangular pillar of 7 × 7 × 101 spins each with uniform magnetization. At low angles, reve… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 8 publications
(12 reference statements)
1
5
0
Order By: Relevance
“…as expected from the Stoner-Wohlfarth model). The effect of the morphology (cylinder compared to the prolate ellipsoid) is given by the lower values of both fields which was confirmed also in previous works [30]. This drop is, of coarse, more visible when the magnetic field is applied along the nanowires (ϕ H = 0 o ) than when they are close to the perpendicular direction (ϕ H = 90 o ).…”
Section: Resultssupporting
confidence: 86%
“…as expected from the Stoner-Wohlfarth model). The effect of the morphology (cylinder compared to the prolate ellipsoid) is given by the lower values of both fields which was confirmed also in previous works [30]. This drop is, of coarse, more visible when the magnetic field is applied along the nanowires (ϕ H = 0 o ) than when they are close to the perpendicular direction (ϕ H = 90 o ).…”
Section: Resultssupporting
confidence: 86%
“…Recent micromagnetic simulation of defect-free d=9 nm Fe nanopillars by Brown et al 26,27 showed that nucleation can start at both ends and propagate through the whole pillars in the time scale of nanoseconds. The calculated H sw is about 2 kOe for the fields applied parallel to the easy axis, which is close to our experimental value.…”
Section: Resultsmentioning
confidence: 99%
“…In this section we summarize recent simulation results for magnetization reversal in iron nanopillars 40 , and further evaluate these results in light of additional experimental data on such reversal. Figure 2a shows hysteresis loops at T = 100 K for the full micromagnetic model with the field misaligned at 0 • , 45 • , and 90 • to the long axis of the particle.…”
Section: Results Of Micromagnetic Simulationsmentioning
confidence: 92%
“…In this section we summarize recent simulation results for magnetization reversal in iron nanopillars 40 , and further evaluate these results in light of additional experimental data on such reversal.…”
Section: Results Of Micromagnetic Simulationsmentioning
confidence: 92%